Investigação de processos colisionais e reacionais para cromo e vanádio em interface de espectrômetro de massa com plasma indutivamente acoplado - Salazar, Rodrigo Fernando dos Santos (Universidade Federal de São Carlos, 2013)
The analytical capability of inductively coupled plasma mass spectrometers (ICPMSs) and their wide use in different fields of science are well known. However some drawbacks, such as the occurrence of isobaric and polyatomic interferences and ionic suppression effects are commonly related to this method, mainly for ICP-MSs with quadrupole analyzers (ICP-QMS). Consequently, some elements as Cr and V are negatively affected due to polyatomic interferences caused by Ar, C, Cl, N, O and S species. Along the development of this method, different strategies were proposed such as dynamic reaction cell technologies (DRC) and collision-reaction interface (CRI) in order to correct for these effects. The aim of this thesis was to evaluate the application of CRI and DRC interfaces for polyatomic interferences correction affecting Cr and V determination. Solutions containing from 1000 up to 10000 mg L-1 of C, Cl, N and S were employed in order to evaluate polyatomic formation and correction of their effects with both devices. Helium and H2 were used as collision reaction gases through the skimmer cone in the ICP-QMS-CRI whereas NH3 was introduced into the DRC-ICP-QMS. These solutions contained 5 Sg L-1 of Cr and V. The figures of merit evaluated were: limits of detection (LOD, ng L-1), background equivalent concentration (BEC, ng L-1) and signal-to-background ratio (SBR) for instrument optimization and sample preparation based on microwave-assisted digestion (MAD), microwave induced combustion (MIC) and sample dilution with internal standardization for different samples were investigated. It was observed that the collision and reaction devices employed led to improvements of SBR, BEC and LOD values for Cr and V from 5 to 100-fold when compared with measurements without using either CRI or DRC. However, signal intensities for Cr and V with both devices decreased when compared with signal intensities obtained with pure analytical solutions. Losses of signal intensities were more critical in ICP-QMS-CRI, independently on the gas (20 mL min-1 He or H2), than in DRC-ICP-QMS (0.5 mL min-1 NH3). Consequently, better LOD and BEC values were achieved for DRC than CRI for Cr and V determinations in crude oil samples from three different sources and lubricant oil. Finally, it could be pointed out that both systems presented advantages and disadvantages that will depend on the analytical task but spectral interferences caused by concomitants could be solved using both devices.
Investigation of collisional and reactional processes for vanadium and chromium in interfaces of inductively coupled plasma mass spectrometer
Keywords: Química analítica; ICP-QMS-CRI; DRC-ICP-QMS; Interferência; Cromo; Vanádio; Óleo cru de petróleo; Interferences; Crude oil; CIENCIAS EXATAS E DA TERRA::QUIMICA